2008
DOI: 10.1038/cdd.2008.65
|View full text |Cite
|
Sign up to set email alerts
|

Living with death: the evolution of the mitochondrial pathway of apoptosis in animals

Abstract: The mitochondrial pathway of cell death, in which apoptosis proceeds following mitochondrial outer membrane permeabilization, release of cytochrome c, and APAF-1 apoptosome-mediated caspase activation, represents the major pathway of physiological apoptosis in vertebrates. However, the well-characterized apoptotic pathways of the invertebrates C. elegans and D. melanogaster indicate that this apoptotic pathway is not universally conserved among animals. This review will compare the role of the mitochondria in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(135 citation statements)
references
References 77 publications
5
122
0
1
Order By: Relevance
“…The absence of an overt phenotype in the CypD/RIPK3-dko mice contrasts with the early lethality and tumor susceptibility usually seen in mutant mice lacking major central pathways of apoptosis (16,47,48) and indicates the predominant involvement of RN mechanisms in severe stress and injury settings as opposed to the physiologic role of apoptosis during development, adult tissue remodeling, and immune system regulation. A similar distinction holds true for at least two of the other RN pathways, pyroptosis (31) and parthanatos (49), because caspase-11-deficient mice that do not undergo pyroptosis and PARP1-deficient mice that do not undergo parthanatos are also viable and fertile.…”
Section: Discussionmentioning
confidence: 77%
“…The absence of an overt phenotype in the CypD/RIPK3-dko mice contrasts with the early lethality and tumor susceptibility usually seen in mutant mice lacking major central pathways of apoptosis (16,47,48) and indicates the predominant involvement of RN mechanisms in severe stress and injury settings as opposed to the physiologic role of apoptosis during development, adult tissue remodeling, and immune system regulation. A similar distinction holds true for at least two of the other RN pathways, pyroptosis (31) and parthanatos (49), because caspase-11-deficient mice that do not undergo pyroptosis and PARP1-deficient mice that do not undergo parthanatos are also viable and fertile.…”
Section: Discussionmentioning
confidence: 77%
“…Apoptosis, by morphological criteria, has unambiguously been described throughout the animals, including Sponges, Cnidaria, Platyhelminthes, Mollusks, Nematodes, Arthropods, Echinoderms, and Chordates, both invertebrate (Ciona) and vertebrate (5). In addition to the C. elegans and Drosophila homologs, homologs of caspases are described in many of these other phyla, as are Bcl-2 homologs (Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators suggested that the mitochondrial 'amplification loop' has been added to the 'core' machinery during the evolution of higher animals. 11 However, another plausible scenario predicts that the link between mitochondrial stress, cytochrome c release and apoptosis induction that regulates intrinsic apoptosis in mammals (and presumably also in a variety of primitive animals including mollusks) 14 has been deleted during the evolution of nematodes (which at the adult stage are mainly composed of post-mitotic cells and hence cannot afford a stress-induced apoptotic default pathway). 15,16 Irrespective of these speculative considerations, it is clear that the pioneering work on C. elegans cell death has inspired the field of mammalian cell death research, especially during the 1980s and the 1990s.…”
Section: The 'Core' Machinery For Cell Death Executionmentioning
confidence: 99%